The Role of Co-Curricular Activities in Improving English Language Speaking Skill of Grade Ten Students at Pinyudo Secondary School in Gog Woreda Gambella, Ethiopia - Kedir Botamo; Joghee Senthilkumar; Bialfew Gizzie (RIRAI Publisher, 2024)
The purpose of this study was to examine the roles of Co-Curricular Activity (CCAs) in improving English language speaking skill of grade ten Students of Secondary School at Gog Woreda in Gambella Regional state. The study was designed using quesi-experimental research design. To collect the necessary data among the existing grade ten students, 44 students selected from section using simple random technique were used as study sample. From these students 22 were assigned as experimental group and the remaining 22 students assigned to form the control group. To data was collected using test as instrument. The data gathered were analyzed using statistical tools such as: means, standard deviations; and significance level were conducted with the T test using Statistical Package for Social Sciences (SPSS version 24). The finding of the study indicated as there was a difference between the experimental and control groups students English speaking performance. In addition, the findings showed as there is significance difference in the mean score of the experimental and control groups of students participated in the study. Moreover, the finding showed as there is difference with regard to aspects of speaking skills between the learners. Based on the findings it was recommended that the school teachers and administration should give high attention for implementation of CCAs in the school integrating it with regular class room lessons. In addition, the school’s teachers and students should conduct experiences sharing with other schools which have better implementation of CCAs. Furthermore, curriculum designers at different level are highly recommended to use CCAs as integral part of regular class room lesson in designing materials. Moreover, future researchers are recommended to make deep investigation including other variables on the area.